Capsule, graphite material and preparation method thereof, pole piece and battery

By introducing capsules and nanometal particles of the capsule wall and capsule core into the graphite material, the problem of performance decay in extreme environments is solved, and excellent cycling performance, conductive performance and high-temperature performance are achieved.

CN119764452APending Publication Date: 2025-04-04SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411972294.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing graphite materials have poor cycling, conductive and high-temperature performance in extreme environments, and are prone to decay of battery performance due to stress accumulation and structural damage.

Method used

A capsule including a capsule wall and a capsule core is adopted, which contains lithium compounds and cycloolefins. The capsule wall is composed of polyurea-formaldehyde resin and is uniformly dispersed with nanometal particles on a graphite substrate to improve the stability and performance of the material.

Benefits of technology

In extreme environments, the capsule can release lithium-containing compounds and cycloolefins during extrusion and rupture, repair the graphite lattice and form a protective film, and improve the cycling, conductive and high-temperature performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764452A_ABST
    Figure CN119764452A_ABST
Patent Text Reader

Abstract

The invention discloses a capsule, a graphite material and a preparation method thereof, a pole piece and a battery. The capsule comprises a capsule wall and a capsule core, wherein the capsule wall is coated on the surface of the capsule core; the capsule core comprises a lithium-containing compound and a cyclic olefin; and the capsule wall comprises a polyurea-formaldehyde resin. When the capsule is applied to a graphite material and a battery, it can maintain excellent cycle performance, electrical conductivity and high temperature performance under extreme environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a capsule, a graphite material and a preparation method thereof, a pole piece and a battery. Background Art

[0002] With the widespread application of lithium-ion batteries in many fields such as electric vehicles and portable electronic devices, the requirements for their performance are also increasing. Although graphite, as a commonly used negative electrode material for lithium-ion batteries, has many advantages, such as low cost and stable potential platform, it still faces some severe challenges during long-term cyclic use. For example, during the repeated insertion and extraction of lithium ions, the lattice structure of graphite will undergo irreversible changes, resulting in stress accumulation inside the material, which in turn causes particle rupture and pulverization. This will not only cause the loss of electrode active substances, reduce the capacity and cycle life of the battery, but may also trigger a series of side reactions, affecting the safety and stability of the battery. In addition, when the battery is subjected to external impact, overcharge, over-discharge, or in extreme environments such as high temperature, the structure of the graphite negative electrode material is more easily damaged, further exacerbating the decline of battery performance, making the existing graphite materials have poor cycle performance, conductivity, and high temperature performance in extreme environments. Summary of the invention

[0003] In order to overcome the defects of low cycle performance, conductivity and high temperature performance of existing graphite materials in extreme environments, the present invention provides a capsule, a graphite material and a preparation method thereof, a pole piece and a battery. When the capsule is used in the graphite material and the battery, it can still maintain excellent cycle performance, conductivity and high temperature performance in extreme environments.

[0004] The present invention solves the above technical problems through the following technical solutions.

[0005] The present invention discloses a capsule, comprising a capsule wall and a capsule core, wherein the capsule wall is coated on the surface of the capsule core;

[0006] The capsule core comprises a lithium-containing compound and a cyclic olefin; and the capsule wall comprises a polyurea-formaldehyde resin.

[0007] In the present invention, polyurea-formaldehyde resin is a thermosetting resin, which is a polymer compound generated by urea and formaldehyde through a polycondensation reaction. Its chemical formula structure is mainly a linear or slightly cross-linked polymer composed of urea groups (-NH-CO-NH-) and methylene groups (-CH2-).

[0008] In the present invention, the lithium-containing compound means a compound containing lithium element.

[0009] In the present invention, the cycloolefin is a type of alicyclic hydrocarbon having a cyclic structure (containing a carbon-carbon double bond on the ring).

[0010] In the present invention, preferably, the maximum particle size of the capsule is 1-3 μm.

[0011] In the present invention, preferably, the thickness of the capsule wall is 0.1-0.2 μm.

[0012] In the present invention, preferably, the shape of the capsule is spherical or elliptical.

[0013] In the present invention, preferably, the lithium-containing compound is lithium bis(oxalatoborate) or lithium bis(fluorosulfonyl)imide, more preferably lithium bis(oxalatoborate).

[0014] In the present invention, preferably, the cycloolefin is cyclopentadiene.

[0015] In the present invention, preferably, the mass ratio of the lithium-containing compound to the cycloolefin is (1-3):1, for example, 2:1.

[0016] In certain specific embodiments of the present invention, the method for preparing the capsule comprises the following steps: mixing a capsule core material and a prepolymer solution and then performing a curing treatment to obtain the capsule; the capsule core material comprises a lithium-containing compound, a cycloolefin and a solvent.

[0017] In certain specific embodiments of the present invention, the core material is in liquid form.

[0018] Wherein, the solvent of the capsule core raw material is, for example, deionized water.

[0019] Preferably, the curing temperature is 50-80°C, for example, 60°C.

[0020] Preferably, the curing treatment time is 2-6 hours, for example, 4 hours.

[0021] Preferably, the method for preparing the prepolymer solution comprises the following steps: mixing urea, formaldehyde and a solvent and performing a prepolymerization reaction to obtain the prepolymer solution.

[0022] The solvent is, for example, deionized water.

[0023] The molar ratio of the urea to the formaldehyde is preferably 1:(1.5-2.5), for example, 1:2.

[0024] Preferably, the mixing method is: adding the capsule core raw material into the prepolymer solution.

[0025] Preferably, the adding is dropwise addition.

[0026] Wherein, the dropping rate is preferably 10-20 mL / min.

[0027] Preferably, after the adding, stirring and ultrasonic steps are sequentially included.

[0028] The stirring speed is preferably 1000-3000 rpm, for example 2000 rpm.

[0029] Wherein, the stirring time is preferably 60-90 minutes.

[0030] The power of the ultrasound is preferably 200-500W, for example 300W.

[0031] The ultrasonic treatment time is preferably 120-150 min.

[0032] Wherein, the prepolymerization reaction can be carried out at normal temperature and pressure.

[0033] In certain specific embodiments of the present invention, the capsule emulsion formed after mixing the capsule core material and the prepolymer solution is in the form of the capsule core material wrapped by the prepolymer.

[0034] In certain specific embodiments of the present invention, the solidification treatment further includes the steps of filtering, washing and drying.

[0035] The present invention also discloses a graphite material, which comprises a graphite substrate, nano-metal particles and the capsules as described above; the capsules and the nano-metal particles are uniformly dispersed on the surface of the graphite substrate in an embedded manner.

[0036] In the present invention, the graphite substrate is a particle, and its particle size is much larger than the particle size of the capsule and the nano-metal particle, so that a plurality of the capsules and the nano-metal particles can be uniformly dispersed on the surface of the graphite substrate in an embedded manner. The embedding means that part or all of the capsules overlap with the surface of the graphite substrate, and part or all of the nano-metal particles overlap with the surface of the graphite substrate.

[0037] In the present invention, the meaning of uniform dispersion is that the difference in distance between any two adjacent capsules does not exceed 1 μm, the difference in distance between any two adjacent nanometal particles does not exceed 1 μm, and the difference in distance between any two adjacent nanometal particles and capsules does not exceed 1 μm.

[0038] In the present invention, the nano metal particles refer to nano-scale metal element single substances and / or compounds containing metal elements.

[0039] In the present invention, preferably, the maximum particle size of the graphite substrate is 15-20 um.

[0040] In the present invention, preferably, the graphite substrate is artificial graphite. The artificial graphite can be a graphite material obtained by using petroleum coke obtained by delayed coking device using petroleum residue oil and then crushing, grinding, graphitization and other processes, and those skilled in the art can know its specific meaning.

[0041] In the present invention, preferably, the mass percentage of the capsule to the graphite substrate is 5%-15%, more preferably 5%-10%, for example, 5.6%, 11.8%, 5.9%, 6.3% or 12.5%.

[0042] In the present invention, preferably, the nano metal particles are nano silver and / or nano copper.

[0043] In the present invention, preferably, the maximum particle size of the nano metal particles is 10-100 nm.

[0044] In the present invention, preferably, the mass percentage of the nano metal particles to the graphite substrate is 5%-20%, preferably 3%-15%, for example 5.6%, 5.9%, 11.8%, 12.5% ​​or 18.8%.

[0045] The present invention also discloses a method for preparing a graphite material, which comprises the following steps:

[0046] The mixture is subjected to hot pressing treatment; the mixture comprises a graphite substrate, nano-metal particles and the capsule as described above;

[0047] Wherein, the temperature of the hot pressing treatment is 100-300°C.

[0048] In the present invention, preferably, the mass percentage of the capsule to the graphite substrate is 5%-15%, more preferably 5%-10%, for example, 5.6%, 11.8%, 5.9%, 6.3% or 12.5%.

[0049] In the present invention, preferably, the mass percentage of the nano metal particles to the graphite substrate is 5%-20%, preferably 3%-15%, for example 5.6%, 5.9%, 11.8%, 12.5% ​​or 18.8%.

[0050] In the present invention, preferably, the graphite substrate is artificial graphite. The artificial graphite may refer to a graphite material obtained by high-temperature treatment of organic carbonization and graphitization, which can generally be obtained by carbonizing and graphitizing a carbonaceous raw material and a binder, and those skilled in the art will know its specific meaning.

[0051] In the present invention, preferably, the maximum particle size of the graphite substrate is 15-20 um.

[0052] In the present invention, preferably, the temperature of the hot pressing treatment is 150-300°C, for example, 200°C.

[0053] In the present invention, preferably, the pressure of the hot pressing treatment is 5-20 MPa, for example, 10 MPa.

[0054] In the present invention, preferably, the heat pressing treatment time is 1-3 hours, for example, 2 hours.

[0055] In certain specific embodiments of the present invention, the heat pressing treatment is carried out in a vacuum heat pressing device.

[0056] In the present invention, preferably, the method for preparing the mixture comprises the following steps: ball milling the graphite substrate, the capsule and the nano-metal particles to obtain the mixture.

[0057] The ball milling is performed in a ball mill, for example.

[0058] The ball milling time is preferably 2-10 h, more preferably 2-8 h, for example 5 h.

[0059] The rotation speed of the ball mill is preferably 200-500 rpm, for example 300 rpm.

[0060] In the present invention, preferably, the nano metal particles are nano silver and / or nano copper.

[0061] In the present invention, preferably, the maximum particle size of the nano metal particles is 10-100 nm.

[0062] In the present invention, the method for preparing the nano metal particles may include the following steps: heating the mixed solution and then centrifuging it; the mixed solution includes a metal salt, a reducing agent and a dispersant.

[0063] Wherein, the reducing agent is, for example, glucose.

[0064] The dispersant is, for example, polyvinyl pyrrolidone.

[0065] The metal salt is, for example, silver nitrate and / or copper nitrate.

[0066] Wherein, the molar ratio of the metal salt to the glucose is 1:(2-5), for example, 1:3.

[0067] Wherein, the molar ratio of the metal salt to the polyvinyl pyrrolidone is 1:(1-2).

[0068] The heating temperature is 40-60°C, for example 50°C.

[0069] The heating time is 1-3 hours, for example, 2 hours.

[0070] In certain specific embodiments of the present invention, the centrifugation is followed by washing and drying steps to obtain nano-metal particles.

[0071] The invention also discloses a graphite material prepared by the preparation method of the graphite material.

[0072] The invention also discloses a pole piece, which comprises the above graphite material.

[0073] In certain specific embodiments of the present invention, the pole piece further comprises conductive carbon black (SP), carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR).

[0074] The mass ratio of the graphite material, the conductive carbon black, the carboxymethyl cellulose and the styrene-butadiene rubber is, for example, 95.5:1.5:1.5:1.5.

[0075] In the present invention, the preparation method of the pole piece may be conventional in the art, for example, comprising the following steps:

[0076] The slurry is coated on a 20um thick copper foil, and the coated copper foil is placed in a 120°C vacuum drying oven and dried for 12 hours to obtain an electrode; the slurry includes the above-mentioned graphite material, conductive carbon black (SP), carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR).

[0077] The invention also discloses a battery, which comprises the pole piece.

[0078] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0079] The reagents and raw materials used in the present invention are commercially available.

[0080] The positive and progressive effects of the present invention are:

[0081] The invention comprises a capsule wall and a capsule core, wherein the capsule core comprises a lithium-containing compound and a cyclic olefin. When applied to graphite materials and batteries, the capsule can be squeezed and ruptured to release the substances therein when subjected to external impact or in an extreme environment. On the one hand, the lithium-containing compound can supplement lithium ions and repair defect sites in the graphite lattice, and on the other hand, the cyclic olefin can form a protective film on the graphite surface to prevent further damage and side reactions. The nano metal particles can not only improve the electrical conductivity, but also play a role of skeleton support, reduce the displacement and rupture of the graphite particles, and make the battery have excellent stability, electrical conductivity, cycle performance and high temperature performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0082] Figure 1 Schematic diagram of the structure of the graphite material of Examples 1-7.

[0083] Figure 2 Schematic diagram of the structure of the capsule in the graphite material of Examples 1-7.

[0084] The reference numerals are as follows:

[0085] 1-graphite substrate; 2-capsule; 3-nanosilver particles;

[0086] 201-cyst wall; 202-cyst core. DETAILED DESCRIPTION

[0087] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0088] The graphite substrate used in the following examples and comparative examples is artificial graphite purchased from Shanghai Shanshan New Materials Co., Ltd., model number PCG-1, and the maximum particle size of the graphite substrate is 20 um.

[0089] Example 1

[0090] Preparation of capsules:

[0091] Dissolving lithium bis(oxalatoborate) and cyclopentadiene in deionized water at a mass ratio of 2:1 to form a capsule core raw material; mixing urea and formaldehyde in a molar ratio of 1:2 with deionized water and performing a prepolymerization reaction at room temperature and pressure to obtain a prepolymer solution;

[0092] The core material was added to the prepolymer solution at a rate of 15 mL / min, stirred at 2000 rpm for 80 min, and then ultrasonicated at 300 W for 130 min to form a capsule emulsion in the form of the core material wrapped by the prepolymer; the capsule emulsion was cured at 60 ° C for 4 h, and then filtered, washed and dried to obtain an elliptical capsule. The maximum particle size of the capsule was 2.5 μm, and the thickness of the capsule wall was 0.2 μm.

[0093] Preparation of Nanometal Particles:

[0094] Silver nitrate, glucose and polyvinyl pyrrolidone are mixed in a molar ratio of 1:3:1 to form a mixed solution, the mixed solution is heated at 50°C for 2 hours, and then centrifuged, washed and dried in sequence to obtain nanosilver. The maximum particle size of the nanosilver is 100nm.

[0095] Preparation of graphite materials:

[0096] The graphite substrate, the capsules and the nano-metal particles were ball-milled at a mass ratio of 90:5:5 in a ball mill at a rotation speed of 300 rpm for 5 hours to obtain a mixture, and the mixture was hot-pressed in a vacuum hot-pressing device for 2 hours to obtain a graphite material. The hot-pressing pressure was 10 MPa and the temperature was 200°C.

[0097] Preparation of pole piece:

[0098] Mix the following raw materials in a mass ratio to prepare a slurry: the above-mentioned graphite material: conductive carbon black (SP): carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 95.5:1.5:1.5:1.5. Apply the slurry on a 20um thick copper foil, and place the coated copper foil in a vacuum drying oven at 120°C and dry it for 12 hours to obtain an electrode.

[0099] Example 2

[0100] Preparation of capsules:

[0101] Dissolving lithium bis(oxalatoborate) and cyclopentadiene in deionized water at a mass ratio of 2:1 to form a capsule core raw material; mixing urea and formaldehyde in a molar ratio of 1:2 with deionized water and performing a prepolymerization reaction at room temperature and pressure to obtain a prepolymer solution;

[0102] The core material was added to the prepolymer solution at a rate of 15 mL / min, stirred at 2000 rpm for 80 min, and then ultrasonicated at 300 W for 130 min to form a capsule emulsion in the form of the core material wrapped by the prepolymer; the capsule emulsion was cured at 60 ° C for 4 h, and then filtered, washed and dried to obtain an elliptical capsule. The maximum particle size of the capsule was 2.5 μm, and the thickness of the capsule wall was 0.2 μm.

[0103] Preparation of Nanometal Particles:

[0104] Silver nitrate, glucose and polyvinyl pyrrolidone are mixed in a molar ratio of 1:3:1 to form a mixed solution, the mixed solution is heated at 50°C for 2 hours, and then centrifuged, washed and dried in sequence to obtain nanosilver. The maximum particle size of the nanosilver is 100nm.

[0105] Preparation of graphite materials:

[0106] The graphite substrate, the capsules and the nano-metal particles were ball-milled at a mass ratio of 85:10:5 in a ball mill at a rotation speed of 300 rpm for 5 hours to obtain a mixture, and the mixture was hot-pressed in a vacuum hot-pressing device for 2 hours to obtain a graphite material. The hot-pressing pressure was 10 MPa and the temperature was 200°C.

[0107] The preparation of the pole piece is the same as that in Example 1.

[0108] Example 3

[0109] Preparation of capsules:

[0110] Dissolving lithium bis(oxalatoborate) and cyclopentadiene in deionized water at a mass ratio of 2:1 to form a capsule core raw material; mixing urea and formaldehyde in a molar ratio of 1:2 with deionized water and performing a prepolymerization reaction at room temperature and pressure to obtain a prepolymer solution;

[0111] The core material was added to the prepolymer solution at a rate of 15 mL / min, stirred at 2000 rpm for 80 min, and then ultrasonicated at 300 W for 130 min to form a capsule emulsion in the form of the core material wrapped by the prepolymer; the capsule emulsion was cured at 60 ° C for 4 h, and then filtered, washed and dried to obtain an elliptical capsule. The maximum particle size of the capsule was 2.5 μm, and the thickness of the capsule wall was 0.2 μm.

[0112] Preparation of Nanometal Particles:

[0113] Silver nitrate, glucose and polyvinyl pyrrolidone are mixed in a molar ratio of 1:3:1 to form a mixed solution, the mixed solution is heated at 50°C for 2 hours, and then centrifuged, washed and dried in sequence to obtain nanosilver. The maximum particle size of the nanosilver is 100nm.

[0114] Preparation of graphite materials:

[0115] The graphite substrate, the capsules and the nano-metal particles were ball-milled at a mass ratio of 85:5:10 in a ball mill at a rotation speed of 300 rpm for 5 hours to obtain a mixture, and the mixture was hot-pressed in a vacuum hot-pressing device for 2 hours to obtain a graphite material. The hot-pressing pressure was 10 MPa and the temperature was 200°C.

[0116] The preparation of the pole piece is the same as that in Example 1.

[0117] Example 4

[0118] Preparation of capsules:

[0119] Dissolving lithium bis(oxalatoborate) and cyclopentadiene in deionized water at a mass ratio of 2:1 to form a capsule core raw material; mixing urea and formaldehyde in a molar ratio of 1:2 with deionized water and performing a prepolymerization reaction at room temperature and pressure to obtain a prepolymer solution;

[0120] The core material was added to the prepolymer solution at a rate of 15 mL / min, stirred at 2000 rpm for 80 min, and then ultrasonicated at 300 W for 130 min to form a capsule emulsion in the form of the core material wrapped by the prepolymer; the capsule emulsion was cured at 60 ° C for 4 h, and then filtered, washed and dried to obtain an elliptical capsule. The maximum particle size of the capsule was 2.5 μm, and the thickness of the capsule wall was 0.2 μm.

[0121] Preparation of Nanometal Particles:

[0122] Silver nitrate, glucose and polyvinyl pyrrolidone are mixed in a molar ratio of 1:3:1 to form a mixed solution, the mixed solution is heated at 50°C for 2 hours, and then centrifuged, washed and dried in sequence to obtain nanosilver. The maximum particle size of the nanosilver is 100nm.

[0123] Preparation of graphite materials:

[0124] The graphite substrate, the capsules and the nano-metal particles were ball-milled at a mass ratio of 90:5:5 in a ball mill at a rotation speed of 300 rpm for 10 hours to obtain a mixture, and the mixture was hot-pressed in a vacuum hot-pressing device for 2 hours to obtain a graphite material. The hot-pressing pressure was 10 MPa and the temperature was 200°C.

[0125] The preparation of the pole piece is the same as that in Example 1.

[0126] Example 5

[0127] Preparation of capsules:

[0128] Dissolving lithium bis(oxalatoborate) and cyclopentadiene in deionized water at a mass ratio of 2:1 to form a capsule core raw material; mixing urea and formaldehyde in a molar ratio of 1:2 with deionized water and performing a prepolymerization reaction at room temperature and pressure to obtain a prepolymer solution;

[0129] The core material was added to the prepolymer solution at a rate of 15 mL / min, stirred at 2000 rpm for 80 min, and then ultrasonicated at 300 W for 130 min to form a capsule emulsion in the form of the core material wrapped by the prepolymer; the capsule emulsion was cured at 60 ° C for 4 h, and then filtered, washed and dried to obtain an elliptical capsule. The maximum particle size of the capsule was 2.5 μm, and the thickness of the capsule wall was 0.2 μm.

[0130] Preparation of Nanometal Particles:

[0131] Silver nitrate, glucose and polyvinyl pyrrolidone are mixed in a molar ratio of 1:3:1 to form a mixed solution, the mixed solution is heated at 50°C for 2 hours, and then centrifuged, washed and dried in sequence to obtain nanosilver. The maximum particle size of the nanosilver is 100nm.

[0132] Preparation of graphite materials:

[0133] The graphite substrate, the capsules and the nano-metal particles were ball-milled at a mass ratio of 90:5:5 in a ball mill at a rotation speed of 300 rpm for 5 hours to obtain a mixture, and the mixture was hot-pressed in a vacuum hot-pressing device for 2 hours to obtain a graphite material. The hot-pressing pressure was 10 MPa and the temperature was 300°C.

[0134] The preparation of the pole piece is the same as that in Example 1.

[0135] Example 6

[0136] Preparation of capsules:

[0137] Dissolving lithium bis(oxalatoborate) and cyclopentadiene in deionized water at a mass ratio of 2:1 to form a capsule core raw material; mixing urea and formaldehyde in a molar ratio of 1:2 with deionized water and performing a prepolymerization reaction at room temperature and pressure to obtain a prepolymer solution;

[0138] The core material was added to the prepolymer solution at a rate of 15 mL / min, stirred at 2000 rpm for 80 min, and then ultrasonicated at 300 W for 130 min to form a capsule emulsion in the form of the core material wrapped by the prepolymer; the capsule emulsion was cured at 60 ° C for 4 h, and then filtered, washed and dried to obtain an elliptical capsule. The maximum particle size of the capsule was 2.5 μm, and the thickness of the capsule wall was 0.2 μm.

[0139] Preparation of Nanometal Particles:

[0140] Silver nitrate, glucose and polyvinyl pyrrolidone are mixed in a molar ratio of 1:3:1 to form a mixed solution, the mixed solution is heated at 50°C for 2 hours, and then centrifuged, washed and dried in sequence to obtain nanosilver. The maximum particle size of the nanosilver is 100nm.

[0141] Preparation of graphite materials:

[0142] The graphite substrate, the capsules and the nano-metal particles were ball-milled at a mass ratio of 80:5:15 in a ball mill at a rotation speed of 300 rpm for 5 hours to obtain a mixture, and the mixture was hot-pressed in a vacuum hot-pressing device for 2 hours to obtain a graphite material. The hot-pressing pressure was 10 MPa and the temperature was 300°C.

[0143] The preparation of the pole piece is the same as that in Example 1.

[0144] Example 7

[0145] Preparation of capsules:

[0146] Dissolving lithium bis(oxalatoborate) and cyclopentadiene in deionized water at a mass ratio of 2:1 to form a capsule core raw material; mixing urea and formaldehyde in a molar ratio of 1:2 with deionized water and performing a prepolymerization reaction at room temperature and pressure to obtain a prepolymer solution;

[0147] The core material was added to the prepolymer solution at a rate of 15 mL / min, stirred at 2000 rpm for 80 min, and then ultrasonicated at 300 W for 130 min to form a capsule emulsion in the form of the core material wrapped by the prepolymer; the capsule emulsion was cured at 60 ° C for 4 h, and then filtered, washed and dried to obtain an elliptical capsule. The maximum particle size of the capsule was 2.5 μm, and the thickness of the capsule wall was 0.2 μm.

[0148] Preparation of Nanometal Particles:

[0149] Silver nitrate, glucose and polyvinyl pyrrolidone are mixed in a molar ratio of 1:3:1 to form a mixed solution, the mixed solution is heated at 50°C for 2 hours, and then centrifuged, washed and dried in sequence to obtain nanosilver. The maximum particle size of the nanosilver is 100nm.

[0150] Preparation of graphite materials:

[0151] The graphite substrate, the capsules and the nano-metal particles were ball-milled at a mass ratio of 80:10:10 in a ball mill at a rotation speed of 300 rpm for 5 hours to obtain a mixture, and the mixture was hot-pressed in a vacuum hot-pressing device for 2 hours to obtain a graphite material. The hot-pressing pressure was 10 MPa and the temperature was 300°C.

[0152] The preparation of the pole piece is the same as that in Example 1.

[0153] The structural schematic diagram of the graphite material prepared in the above examples 1-7 is as follows Figure 1 and Figure 2As shown, it includes a graphite substrate 1, capsules 2 and nano-silver particles 3, the capsules and nano-silver are uniformly dispersed in the surface layer of the graphite substrate in an embedded manner, the capsule includes a capsule wall 201 and a capsule core 202, the capsule wall 201 is coated on the surface of the capsule core 202, and the capsule core includes a lithium-containing compound and a cycloolefin. The graphite substrate is a particle, and its particle size is much larger than the particle size of the capsule and the nano-metal particle, so that multiple capsules and multiple nano-metal particles can be uniformly dispersed in the surface layer of the graphite substrate in an embedded manner. Among them, the meaning of embedded means that part or all of the capsules overlap with the surface layer of the graphite substrate, and part or all of the nano-metal particles overlap with the surface layer of the graphite substrate. The meaning of uniform dispersion is that the difference in distance between any two adjacent capsules does not exceed 1μm, the difference in distance between any two adjacent nano-metal particles does not exceed 1μm, and the difference in distance between any two adjacent nano-metal particles and capsules does not exceed 1μm.

[0154] In the graphite materials prepared in the above embodiments 1-7, the mass percentage of capsules in the graphite substrate and the mass percentage of nanosilver in the graphite substrate are listed in the following Table 1; the specific calculation method is: the masses of the graphite substrate, capsules and nanosilver before and after being put into the ball mill are weighed respectively, the mass of the graphite substrate in the graphite material is calculated as the mass of the graphite substrate before being put into the ball mill-the mass of the graphite substrate after ball milling, the mass of the capsules in the graphite material is calculated as the mass of the capsules before being put into the ball mill-the mass of the capsules after ball milling, and the mass of the nanosilver in the graphite material is calculated as the mass of the nanosilver before being put into the ball mill-the mass of the nanosilver after ball milling; the mass percentage of the capsules in the graphite substrate is calculated as the mass of the capsules in the graphite material / the mass of the graphite substrate, and the mass percentage of the nanosilver in the graphite substrate is calculated as the mass of the nanosilver in the graphite material / the mass of the graphite substrate.

[0155] Table 1

[0156]

[0157] Comparative Example 1

[0158] Pure graphite is used as the graphite material.

[0159] The preparation of the pole piece is the same as that in Example 1.

[0160] Comparative Example 2

[0161] The preparation conditions of capsules and nano-metal particles are the same as those in Example 1.

[0162] Preparation of graphite materials:

[0163] The graphite substrate and the capsule were ball-milled at a mass ratio of 90:5 in a ball mill at a rotation speed of 300 rpm for 5 hours to obtain a mixture, and the mixture was hot-pressed in a vacuum hot-pressing device for 2 hours to obtain a graphite material. The hot-pressing pressure was 10 MPa and the temperature was 200°C.

[0164] The preparation of the pole piece is the same as that in Example 1.

[0165] Comparative Example 3

[0166] The preparation conditions of capsules and nano-metal particles are the same as those in Example 1.

[0167] Preparation of graphite materials:

[0168] The graphite substrate and nano-metal particles were ball-milled at a mass ratio of 90:5 in a ball mill at a rotation speed of 300 rpm for 5 hours to obtain a mixture, and the mixture was hot-pressed in a vacuum hot-pressing device for 2 hours to obtain a graphite material. The hot-pressing pressure was 10 MPa and the temperature was 200°C.

[0169] The preparation of the pole piece is the same as that in Example 1.

[0170] Comparative Example 4

[0171] Preparation of capsules:

[0172] Dissolving lithium dioxalatoborate in deionized water to form a capsule core raw material; mixing urea and formaldehyde in a molar ratio of 1:2 and performing a prepolymerization reaction to obtain a prepolymer solution;

[0173] The core material was added to the prepolymer solution at a rate of 15 mL / min, stirred at 2000 rpm for 80 min, and then ultrasonicated at 300 W for 130 min to form a capsule emulsion in the form of the core material wrapped by the prepolymer; the capsule emulsion was cured at 60 ° C for 4 h, and then filtered, washed and dried to obtain an elliptical capsule. The maximum particle size of the capsule was 2 μm, and the thickness of the capsule wall was 0.15 μm.

[0174] The preparation conditions of nano metal particles and graphite materials are the same as those in Example 1.

[0175] The preparation of the pole piece is the same as that in Example 1.

[0176] Comparative Example 5

[0177] Preparation of capsules:

[0178] Dissolving cyclopentadiene in deionized water to form a capsule core raw material; mixing urea and formaldehyde in a molar ratio of 1:2 and performing a prepolymerization reaction to obtain a prepolymer solution;

[0179] The core material was added to the prepolymer solution at a rate of 15 mL / min, stirred at 2000 rpm for 80 min, and then ultrasonicated at 300 W for 130 min to form a capsule emulsion in the form of the core material wrapped by the prepolymer; the capsule emulsion was cured at 60 ° C for 4 h, and then filtered, washed and dried to obtain an elliptical capsule. The maximum particle size of the capsule was 2 μm, and the thickness of the capsule wall was 0.15 μm.

[0180] The preparation conditions of nano metal particles and graphite materials are the same as those in Example 1.

[0181] The preparation of the pole piece is the same as that in Example 1.

[0182] Comparative Example 6

[0183] The preparation conditions of capsules and nano-metal particles are the same as those in Example 1.

[0184] Preparation of graphite materials:

[0185] The graphite substrate, the capsules and the nano-metal particles were ball-milled at a mass ratio of 90:5:5 in a ball mill at a rotation speed of 300 rpm for 5 hours to obtain a mixture, and the mixture was hot-pressed in a vacuum hot-pressing device for 2 hours to obtain a graphite material. The hot-pressing pressure was 10 MPa and the temperature was 50°C.

[0186] The preparation of the pole piece is the same as that in Example 1.

[0187] Comparative Example 7

[0188] The preparation conditions of capsules and nano-metal particles are the same as those in Example 1.

[0189] Preparation of graphite materials:

[0190] The graphite substrate, the capsules and the nano-metal particles were ball-milled at a mass ratio of 90:5:5 in a ball mill at a rotation speed of 300 rpm for 5 hours to obtain a mixture, and the mixture was hot-pressed in a vacuum hot-pressing device for 2 hours to obtain a graphite material. The hot-pressing pressure was 10 MPa and the temperature was 400°C.

[0191] The preparation of the pole piece is the same as that in Example 1.

[0192] Effect Example 1

[0193] Assembly of half-cell:

[0194] The pole pieces of Examples 1-7 and Comparative Examples 1-7 were assembled into half-cells in an argon-protected glove box. The electrolyte was 1M LiPF6, EC, DEC, and DMC (the volume ratio of EC, DEC, and DMC was 1:1:1). A metal lithium sheet was used as the counter electrode. The following tests were performed on the above half-cells in a blue battery test cabinet:

[0195] 1. First charge specific capacity and first charge and discharge efficiency: The charge and discharge voltage is 0.001V-2V, the charge / discharge rate is 1C, and the first charge specific capacity and first charge and discharge efficiency are recorded.

[0196] 2. 5000-cycle capacity retention rate: The charge and discharge voltage is 0.001V-2V, the charge / discharge rate is 1C, and the discharge capacity before and after 5000 cycles of the battery is recorded respectively. 5000-cycle capacity retention rate = discharge capacity after 5000 cycles / discharge capacity before 5000 cycles.

[0197] 3. Impedance (EIS) test: Place the half-cell on an electrochemical workstation, set the frequency scan range to 1 MHz to 0.1 Hz for testing, and record the EIS value of the battery.

[0198] Assembly of the full battery:

[0199] The pole pieces of Examples 1-7 and Comparative Examples 1-7 were assembled with lithium cobalt oxide positive pole pieces into full batteries, and the electrolyte was 1M LiPF6, EC, DEC, DMC (the volume ratio of EC, DEC, DMC was 1:1:1), and the following tests were performed on the full batteries:

[0200] 4. High temperature storage capacity recovery rate: The operating voltage range is 3.00-4.50V, and the high temperature storage (85℃&8h) test is carried out at 100% SOC.

[0201] The above test results are listed in Table 2 below:

[0202] Table 2

[0203]

[0204]

[0205] According to the results in the above table, when the graphite material prepared in the embodiment of the present invention is applied to a battery, its 5000-cycle capacity retention rate can reach more than 90.4%, indicating that the embodiment of the present invention has excellent cycle performance; its high-temperature storage capacity recovery rate can reach more than 91.1%, indicating that the embodiment of the present invention has excellent high-temperature performance; at the same time, the graphite material of the present invention is applied to the battery for the first charge specific capacity to reach more than 338.3 mAh / g, the first charge and discharge efficiency can reach more than 91.3%, and the EIS can reach less than 4.5Ω.

[0206] Comparative Example 1 uses pure graphite to replace the graphite material of the present invention, resulting in an EIS of 8.6Ω, a 5000-cycle capacity retention rate of only 47.5%, and a high-temperature storage capacity recovery rate of only 78.3%, indicating that the cycle performance, conductive performance, and high-temperature performance of Comparative Example 1 are significantly reduced.

[0207] The graphite material of Comparative Example 2 does not contain nanosilver, resulting in a decrease in its cycle performance, conductivity and high temperature performance. The graphite material of Comparative Example 3 does not contain capsules, resulting in a decrease in its cycle performance and high temperature performance. The capsules of Comparative Example 4 do not contain cyclopentadiene, and the capsules of Comparative Example 5 do not contain lithium bis(oxalate borate), resulting in a decrease in its cycle performance and high temperature performance. The temperature of the hot pressing treatment of Comparative Example 6 is too low, and the temperature of the hot pressing treatment of Comparative Example 7 is too high, resulting in a decrease in its cycle performance and high temperature performance.

Claims

1. A capsule, characterized in that: The capsule comprises a capsule wall and a capsule core, wherein the capsule wall is coated on the surface of the capsule core; The capsule core comprises a lithium-containing compound and a cyclic olefin; and the capsule wall comprises a polyurea-formaldehyde resin.

2. The capsule according to claim 1, characterized in that The maximum particle size of the capsule is 1-3 μm; And / or, the thickness of the capsule wall is 0.1-0.2 μm; and / or, the capsule is spherical or elliptical in shape; And / or, the lithium-containing compound is lithium bis(oxalatoborate) or lithium bis(fluorosulfonyl)imide, preferably lithium bis(oxalatoborate); and / or, the cycloolefin is cyclopentadiene; And / or, the mass ratio of the lithium-containing compound to the cycloolefin is (1-3):1, for example, 2:

1.

3. The capsule according to claim 1 or 2, characterized in that The preparation method of the capsule comprises the following steps: mixing a capsule core raw material and a prepolymer solution and then performing a curing treatment to obtain the capsule; the capsule core raw material comprises a lithium-containing compound, a cycloolefin and a solvent; Wherein, the solvent of the capsule core raw material is, for example, deionized water; Preferably, the curing temperature is 50-80°C, for example, 60°C; Preferably, the curing time is 2-6 hours, for example, 4 hours; Preferably, the preparation method of the prepolymer solution comprises the following steps: mixing urea, formaldehyde and a solvent and then performing a prepolymerization reaction to obtain the prepolymer solution; wherein the solvent is, for example, deionized water; wherein the molar ratio of the urea to the formaldehyde is preferably 1:(1.5-2.5), for example, 1:2; preferably, the mixing method is: adding the capsule core raw material to the prepolymer solution; preferably, the adding is dropwise addition; wherein the dropwise addition rate is preferably 10-20 mL / min; wherein, after the adding, preferably, stirring and ultrasonic steps are also included in sequence; wherein the stirring speed is preferably 1000-3000 rpm, for example, 2000 rpm; wherein the stirring time is preferably 60-90 min; wherein the ultrasonic power is preferably 200-500 W, for example, 300 W; wherein the ultrasonic time is preferably 120-150 min.

4. A graphite material, characterized in that: The graphite material comprises a graphite substrate, nano-metal particles and capsules as described in any one of claims 1 to 3; the capsules and the nano-metal particles are uniformly dispersed on the surface of the graphite substrate in an embedded manner.

5. The graphite material according to claim 4, characterized in that The maximum particle size of the graphite substrate is 15-20um; And / or, the graphite substrate is artificial graphite; And / or, the mass percentage of the capsules to the graphite substrate is 5%-15%, more preferably 5%-10%, for example, 5.6%, 6.8%, 7.9%, 8.3% or 9.5%; And / or, the nano metal particles are nano silver and / or nano copper; And / or, the maximum particle size of the nano metal particles is 10-100 nm; And / or, the mass percentage of the nano metal particles to the graphite substrate is 5%-20%, preferably 3%-15%, for example, 5.6%, 5.9%, 11.8%, 12.5% ​​or 14.8%.

6. A method for preparing a graphite material, characterized in that: It includes the following steps: The mixture is subjected to hot pressing; the mixture comprises a graphite substrate, nano-metal particles and a capsule as described in any one of claims 1 to 3; Wherein, the temperature of the hot pressing treatment is 100-300°C.

7. The method for preparing a graphite material according to claim 6, characterized in that: The mass percentage of the capsule to the graphite substrate is 5%-15%, more preferably 5%-10%, for example, 5.6%, 11.8%, 5.9%, 6.3% or 12.5%; And / or, the mass percentage of the nano metal particles to the graphite substrate is 5%-20%, preferably 3%-15%, for example, 5.6%, 5.9%, 11.8%, 12.5% ​​or 18.8%; And / or, the graphite substrate is artificial graphite; And / or, the maximum particle size of the graphite substrate is 15-20 um; And / or, the temperature of the hot pressing treatment is 150-300° C., for example, 200° C.; And / or, the pressure of the hot pressing treatment is 5-20 MPa, for example, 10 MPa; And / or, the heat pressing treatment time is 1-3 hours, for example, 2 hours; And / or, the preparation method of the mixture comprises the following steps: ball milling the graphite substrate, the capsule and the nano metal particles to obtain the mixture; Wherein, the ball milling is carried out in a ball mill, for example; The ball milling time is preferably 2-10 hours, more preferably 2-8 hours, for example 5 hours; Wherein, the rotation speed of the ball mill is preferably 200-500 rpm, for example, 300 rpm; And / or, the nano metal particles are nano silver and / or nano copper; And / or, the maximum particle size of the nano metal particles is 10-100 nm; And / or, the method for preparing the nano metal particles comprises the following steps: heating the mixed solution and then centrifuging it; the mixed solution comprises a metal salt, a reducing agent and a dispersant; Wherein, the reducing agent is, for example, glucose; wherein, the dispersing agent is, for example, polyvinyl pyrrolidone; wherein, the metal salt is, for example, silver nitrate and / or copper nitrate; wherein, the molar ratio of the metal salt to the glucose is 1:(2-5), for example, 1:3; wherein, the molar ratio of the metal salt to the polyvinyl pyrrolidone is 1:(1-2); Wherein, the heating temperature is 40-60°C, for example, 50°C; The heating time is 1-3 hours, for example, 2 hours.

8. A graphite material obtained by the method for preparing a graphite material according to claim 6 or 7.

9. A pole piece, characterized in that: It comprises the graphite material as claimed in any one of claims 4-5 and 8.

10. A battery, characterized in that: It comprises the pole piece as claimed in claim 9.